Ball impact localization on table tennis rackets using piezo-electric sensors - Blank, Peter; Kautz, Thomas; Eskofier, Björn (Proceedings of the 2016 ACM International Symposium on Wearable Computers, 2016)
In this paper, we present an approach for a ball impact localization on table tennis rackets using piezo-electric sensors. Three sensors were used as vibration sensors at the outer edge of the racket. We analyzed ball impact vibration appearances and measured time differences of arriving wave fronts for each sensor pair. A study was conducted comprising six different racket-rubber combinations. Firstly, we calculated a time difference distribution model based on training sets of impact data constructed by a grid of measuring points. Secondly, this model was used to estimate the impact position of test data sets using three different methods. Best performance for each racket-rubber combination was achieved with a linear regression based method yielding a RMSE in x-direction (transversal racket direction) of 22.1 mm and a RMSE of 19.8 mm in y-direction (longitudinal racket direction). The measuring system is small enough to be completely invisibly integrated into table tennis rackets. This contribution is the first attempt to address a ball impact localization system for table tennis rackets that has the potential to be used in real-world training exercises and competitions to assist table tennis players during matches and to support the athletes' training progress.
Keywords: piezo-electric sensors; vibration measurement; localization; table tennis